GAMBARAN KARAKTERISTIK PASIEN DENGAN GOUT ARTHRITIS - Lawva Desverisca; Darwin Karim; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Gout arthritis is a metabolic disease characterized by the deposition of uric acid compounds in the joint causing pain in the joints. The incidence of gout arthritis is caused by various risk factors such as genetics, age, gender, excess weight and diet. The purpose of this study was to describe the characteristics of patients with gout arthritis. The quantitative descriptive research design uses a cross sectional method. The sample in this study amounted to 57 respondents taken based on inclusion criteria using purposive sampling. The instrument used was a demographic questionnaire and a food frequency questionnaire (FFQ). The results of the study were obtained by the majority of respondents were early elderly (45.6%), gender was female (77.2%), the last education was elementary (35.1%), the majority of the respondents were Malay (43.9%), frequency pain that often arises is in the morning totaling 28 people (49.1%), long suffering from pain> 6 months / chronic pain (66.7%), action/treatment that is taking anti-pain medication (50.9%), physical activity mild (89.5%), no family history with gout arthritis (66.7%), and a diet containing purine intake always consumed tempeh (31.6%), tofu (33.3%) and beans (17.5%). It is recommended to the health center to increase public knowledge by providing counseling related to planning prevention of the occurrence of gout arthritis. Keywords: Characteristics, gout arthritis, overview